Serum sodium and potassium levels as prognostic indicators in pediatric diabetic ketoacidosis - Hamza Mullath; Sridevi A Naaraayan (Wolters Kluwer Medknow Publications, 2019)
Introduction : Diabetic ketoacidosis (DKA),a common emergency encountered in children is characterized by deranged acid-base status and a myriad of electrolyte disturbances. Objective : This study was done with the objective of determining the effect of serum sodium and potassium levels on prognosis of children with DKA. Methods : This cross-sectional study was done in the pediatric intensive care unit of a tertiary care center, from January 2015 to September 2015. Children diagnosed with DKA were included in the study. Convenient sample size was adopted. In a structured proforma, demographic and medical history was noted. Serum sodium and potassium were determined by Ion Selective Electrode method at the time of diagnosis and 12 hourly, till resolution of acidosis. The clinical outcome of the child, the duration of insulin infusion and hospital stay were noted. Association between dependent and independent variables was determined by chi-square test and level of significance was fixed at 5%. Results : Thity three patients were included. The mortality rate was 13%. Twenty (60%) patients required insulin infusion for less than 24 hours and 18 (62%) stayed in hospital for less than 2 weeks. Hyperkalemia at presentation was significantly associated with mortality, hyponatremia at the time of admission was found to be significantly associated with prolonged hospital stay and abnormal sodium and potassium levels persisting at the end of 24 hours was significantly associated with need for prolonged insulin infusion. Conclusion : Presence of hyperkalemia and hyponatremia at admission and persistence of abnormal serum sodium and potassium levels beyond 24 hours are poor prognostic markers in children with DKA.